THU0091 DEPRESSION IN PATIENTS WITH RHEUMATOID ARTHRITIS: UNDER RECOGNIZED, UNDERTREATED AND ASSOCIATED WITH POORER CLINICAL STATUS AND LOWER RATES OF REMISSION IN ROUTINE CARE. (June 2019) - Morla, Rosa; Riad, Mariam; Pincus, Theodore; Castrejon, Isabel
Abstract : Background: Depression in patients with rheumatoid arthritis (RA) may be pre-existent, amplified, or newly-developed after onset of RA. Together with other comorbidities, socioeconomic, or affective factors can influence perception of pain, functional disability, and health status. The prevalence of depression in RA patients is 19% and affect remission rates according to a classical composite index. 1 Objectives: We compared patient self-reported scores included on the Multidimensional Health-Assessment Questionnaire (MDHAQ) and levels of remission according to RAPID3 in patients who self-reported depression versus no depression. Methods: All patients complete a MDHAQ at each visit, which includes physical function (FN), three 0-10 visual analogue scales (VAS) for pain (PN), patient global estimate (PATGL), fatigue (FT), RADAI self-report joint count, a review of 60 symptoms (ROS) on a checklist, three evaluations for depression, anxiety and sleep quality (0-3.3), and demographics. RAPID3 (0-30) is the sum of FN, PN, and PATGL; being remission RAPID3 <3. Patients with RA (ICD10) were classified according to self-reported depression on the ROS. Agreement between MDHAQ-depression and by the Patient Health Questionnaire (PHQ-9) was evaluated in 57 patients. Demographic and clinical characteristics were compared by self-reported depression status using Student t-test and chi-square test. Results: 464 RA patients were studied: 118 (25%) self-reported depression. In 57 patients, who also completed the PDQ-9, agreement with MDHAQ depression was 93% (kappa=0.80 95% IC 0.61-0.99). Only 37 (31%) of all patients reporting depression had evidence in the medical record of treatment and/or specialist evaluation for depression. No differences between depression groups were seen for mean age or sex. Patients reporting depression had lower education level (12.5 vs 14.3, p<0.001) and poorer scores for physical function, pain, and patient global leading to higher RAPID3 and lower percentage of patient in remission (12.4 vs 4%, p<0.001) (Table). Depressed patients also reported higher scores for fatigue, number of painful joints, number or symptoms, and more difficulty with sleep, and anxiety. Table: MDHAQ patient self-report scores in patients with RA according to depression status. Data are presented as mean (SD) and percentages. *p<0.001 Conclusion: The prevalence of self-reported depression in our RA patients was 25%, with only 31% treated for this condition. RA patients with self-reported depression exhibit higher scores for all MDHAQ scores, and a lower rate of RAPID3 remission. MDHAQ may be useful to identify patients with depression in busy clinical settings. Reference: [1] Leblanc-Trudeau, C, et al. Rheumatology 2015;54:2205-14. Disclosure of Interests: None declared